Effect of strain rate on the mechanical properties of a gum metal with various microstructures. (15th June 2017) - Liu, Silu; Pan, Z.L.; Zhao, Y.H.; Topping, T.; Valiev, R.Z.; Liao, X.Z.; Lavernia, E.J.; Zhu, Y.T.; Wei, Q.
Abstract: In this work, a bulk gum metal (GM) was fabricated via arc melting from high purity powders. The ingots were first extruded using a conventional route followed by equal channel angular pressing (ECAP). The mechanical behavior of the extruded GM and ECAP-processed GM was studied under both quasi-static and high strain rate compression conditions to evaluate the influence of strain rate. In addition, the associated mechanical anisotropy, or the lack thereof, was investigated through loading in different orientations with respect to the extrusion or ECAP direction. Precipitous stress drops were observed under dynamic compression of both extruded and ECAP-processed GM specimens when loading perpendicular to the extrusion direction. Adiabatic shear banding (ASB) was found to be associated with the precipitous stress drops on the dynamic stress-strain curves. The details of the ASBs were characterized by optical and scanning electron microscopy, with emphasis on electron backscattered diffraction (EBSD). The mechanisms responsible for the formation of ASB were examined both from thermal softening and geometrical softening perspectives. Significant microstructure refinement within ASBs was established, and a possible grain refinement mechanism was proposed. Graphical abstract: Image